The many faces and facets of war: redrawing the boundaries and focus of warfare in contemporary international affairs / Tang Siew Mun - Tang, Siew Mun (Centre for Media and Information Warfare Studies, 2008)
From the times of the Roman legion to the thunderous roar of the Soviet T-34 tanks, wars have shaped and literally drawn the boundaries of humanity. Although wars in contemporary times are less frequent than a few centuries ago, modern wars are more lethal and destructive. It is this singular feature -large scale destruction- that sets wars apart from other forms of conflict. Wars have been waged in various intensities and degrees and by diverse actors, but have traditionally been seen as the domain of states. In medieval times, wars were the "sports" of kings. Conceptually, war is defined as an armed conflict involving at least two nation-states. How does this characterization of war explain the types of conflicts that imperil a state's national interest and well-being without the use of force? How does this definition reconcile itself with the almost "war-like" threats posed by non-state actors? How does a state defend itself against foreign penetration and dissemination of information detrimental to its political stability and survival? This paper addresses these issues and argues that the traditional definition of war is too narrow. Wars are fought on many fronts and may not necessarily involve the use of armed violence. Globalization has brought to the fore new challenges to state sovereignty and security. Issues such as trade wars and the spread of pandemic diseases do not fall under the traditional understanding of "war" but are no less lethal and destructive. This calls for a broader definition of war to encompass dimensions of non-militarized conflicts and means of engagement.